Optimizing Social Studies Learning in Early Elementary School Grades: Strategies and Challenges - Haifa Annisa; Lailatul Qurrota Ayuni; Ismi Rahmayanti; Tin Rustini (Amandemen: Journal of Learning, Teaching and Educational Studies, 2024)
Social Studies learning in early elementary grades plays a crucial role in shaping students' understanding and awareness of their social and cultural environment. However, in practice, Social Studies learning at this level often faces various challenges. This article aims to examine strategies and challenges in optimizing Social Studies learning in early elementary grades. The research method used is a literature study by analyzing various sources related to Social Studies learning in early elementary grades. The findings suggest that several strategies can be implemented to optimize Social Studies learning, including (1) the use of thematic-integrative approaches, (2) the utilization of engaging and interactive learning media, (3) the application of student-centered learning methods, and (4) the development of critical thinking and problem-solving skills. On the other hand, the challenges faced in optimizing Social Studies learning include (1) teachers' limited understanding of the concepts and characteristics of Social Studies learning, (2) the lack of adequate facilities and infrastructure, (3) a dense curriculum load, and (4) difficulties in relating Social Studies material to students' daily lives. The article concludes that optimizing Social Studies learning in early elementary grades requires comprehensive efforts, including improving teacher competencies, providing adequate learning resources, and adjusting the curriculum to meet the needs and characteristics of students. Thus, Social Studies learning in early elementary grades can lay a strong foundation for the development of students' understanding and awareness of their social and cultural environment.